PERBANDINGAN PENGARUH EVA DAN PENGUKURAN KINERJA LAINNYA TERHADAP IMBAL HASIL SAHAM DI INDONESIA - Hidayat, Taufik (UI Scholars Hub, 2006)
The purpose o f this study is to examine whether Economic Value Added9 (EVA) is more highly associated with stock returns than other conventional accounting- based measures such as Earnings before Extraordinary Items, Cash Flow from Operation, and Residual Income, as claimed by Stern Stewart. Using pooled ordinary least square method or Panel Data on 121 Indonesian- listed companies in Jakarta Stock Exchange over the period 2001-2003, the test emphasizp on two approaches. Relative Information Content describes the association ofeach individual performance measure relatively with stock returns and Incremental Information Content describes the association of each performance measure with stock return individually and simultaneously. The relative information content tests reveal that earnings to be more closely associated with stock returns than EVA®, Cash Flow from Operation, and Residual Income. The incremental information content tests reveal that earnings and Cash Flow from Operation to be more closely associated with stock returns than EVA® and Residual Income. Other tests for components of EVA® reveal only Cash Flow from Operation and Accruals to be significantly associated with stock returns, where Cash Flow from Operation and Accruals are equal with earnings.